Distribution, variation, and relationship of Curcuma soloensis Valeton in Java, Indonesia based on morphological characters - MUHAMAD JALIL; AZIZ PURWANTORO; BUDI SETIADI DARYONO; Purnomo PURNOMO (Society for Indonesian Biodiversity, 2020)
Abstract. Jalil M, Purwantoro A, Daryono BS, Purnomo. 2020. Distribution, variation, and relationship of Curcuma soloensis Valeton in Java, Indonesia based on morphological characters. Biodiversitas 21: 3867-3877. Curcuma soloensis Valeton (locally called temu genyeh) was a plant originating from Solomon Islands and was synonymous with Curcuma longa L. This plant was often considered to be turmeric (Curcuma longa Linn.) or temulawak (Curcuma zanthorrhiza Roxb.), because the rhizome is almost the same color. The purpose of this study was to determine the distribution, variation, and relationship of C. soloensis in Java, Indonesia. Retrieval of data with exploratory roaming methods in 12 districts/cities in Java Island as a center for planting medicinal plants. Morphological character observations were made on habit, rhizome, roots, tubers, leaves, pseudo-stems, and flowers. Morphological data were analyzed by descriptive and numerical methods. Analysis of grouping with Gower Coefficients because it uses 45 binary and multistate data. Principal Component Analysis (PCA) was performed to determine the role of each character in the grouping. Cluster analysis and PCA graphics were assisted with MVSP 3.1 software. The results of the study were obtained from 25 accessions of C. soloensis in East Java (Trenggalek, Pacitan, Ponorogo), Central Java (Wonogiri, Karanganyar, Magelang, Semarang), Yogyakarta (Yogyakarta City, Bantul, Gunungkidul), and West Java (Ciamis and Tasikmalaya). The variation of C. soloensis lies in habit, stem color, leaf shape, rhizome shape, rhizome flesh color, and tuber shape. The highest abundance percentage is in Pajangan, Tirtomoyo, and Tawangmangu. The dendrogram divides 32 OTUs into two clusters on the phenon line 0.617, namely cluster A (C. zanthorrhiza) and cluster B (C. soloensis and C. longa). PCA results showed that the characters that had the most role in grouping were leaf blade color, leaf blade length, rhizome shape, root color, rhizome taste, outer and inner rhizome flesh color.